2009
DOI: 10.5539/ijbm.v4n7p26
|View full text |Cite
|
Sign up to set email alerts
|

Decision Orientations towards Shopping and Buying among Young-Adult Malays in the Universities

Abstract: The learning processes that every consumer goes through would be the determining factors to the decisions a consumer makes when one is purchasing a product or paying for a service. Consumer educators and those involved with consumer interest studies in general consider the above statement as extremely obvious even though one might assume that consumers' learning and decision-making are a related phenomenon. In essence, such relationship has not been systematically explored in consumer research (Sproles & Sprol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Our study is directed towards understanding the influence of materialism and religiosity on consumer choice and the desire for the material products such as fashion clothing. Malaysia is considered an attractive market because of the young adult representation in lucrative market segment and the increase in purchasing power (Mokhlis, 2009a;Salleh, 2009a, 2009b;Wan Omar et al, 2009;Ali et al, 2015). Despite the fact that majority of the young adults are college students and unemployed, college students represent a significant market segment for many products and services Salleh, 2009a, 2009b;Moschis and Cox, 1989).…”
Section: Fashion Clothing Purchasementioning
confidence: 99%
“…Our study is directed towards understanding the influence of materialism and religiosity on consumer choice and the desire for the material products such as fashion clothing. Malaysia is considered an attractive market because of the young adult representation in lucrative market segment and the increase in purchasing power (Mokhlis, 2009a;Salleh, 2009a, 2009b;Wan Omar et al, 2009;Ali et al, 2015). Despite the fact that majority of the young adults are college students and unemployed, college students represent a significant market segment for many products and services Salleh, 2009a, 2009b;Moschis and Cox, 1989).…”
Section: Fashion Clothing Purchasementioning
confidence: 99%
“…Since its introduction, there has been a series of investigation aimed at testing the generalizability of the CSI across different countries: the USA (Lysonski, Durvasula & Zotos, 1996;Wickliffe, 2004), South Korea (Hafstrom, Chae & Chung, 1992;Wickliffe, 2004), China (Fan & Xiao, 1998;Hiu, Siu, Wang & Chang, 2001), New Zealand (Durvasula, Lysonski & Andrews, 1993;Lysonski et al, 1996), Greece (Lysonski et al, 1996), India (Lysonski et al 1996;Canabal, 2001), Germany (Walsh, Mitchell & Thurau, 2001), UK (Mitchell & Bates, 1998), South Africa (Radder, Li & Pietersen, 2006), Turkey (Gonen & Ozmete, 2006), Brazil (Dos Santos & Fernandes, 2006), Iran (Hanzaee & Aghasibeig, 2008) and Malaysia (Mokhlis, 2009;Wan Omar et al 2009). These studies confirmed varying portions of the original CSI, indicating that the US eight factors are not consistent in other cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Radder et al's (2006) study is the only exception that examines decision-making styles of Chinese, Motswana and Caucasian students in South Africa. In Malaysia, two published studies on decision-making styles are identified, namely Mokhlis (2009) and Wan Omar et al (2009), both of which sampled the student market. While these two studies provided important insights into consumer behavior within the specific context of Malaysia, the studies did not looked at ethnic variation in consumer decision-making styles.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some attempts to identify differences in decision-making between Eastern and Western cultures in past research (Omar, Ali, Hussin, & Rahim, 2009). For example, decision-making in collectivist cultures is generally a group activity (Doran, 2002).…”
Section: Individualism-collectivism and Consumer Decision Makingmentioning
confidence: 99%